Chemistry Teachers’ Self-efficacy for Using Information and Communication Technology: A Survey Cross Sectional - Insani Efrili Yanti; Hari Sutrisno (Jurnal Penelitian Pendidikan IPA, 2024)
The utilization of ICT in education could be further optimized due to the low self-efficacy of teachers. Teachers' years of teaching experience and the status of their schools have an influence on their ICT self-efficacy. This study aims to describe the differences in ICT self-efficacy among chemistry teachers based on their teaching experience and school status. This study used a quantitative approach with a cross-sectional survey method. The research was conducted in 31 high schools in Pekanbaru City and included a randomly selected sample of 50 chemistry teachers. The research instruments consisted of ICT self-efficacy questionnaires 14 items. ICT self-efficacy instrument declared valid and reliable using the Rasch model test. Additionally, interview data were employed to reinforce the findings from the questionnaire. The research questionnaire data underwent processing using analysis descriptive statistics and a two-way ANOVA test with SPSS. The results of the research show that there is a significant difference in the ICT self-efficacy of chemistry teachers based on the teacher's teaching experience with significance level of 0.005 and there is no difference the ICT self-efficacy of chemistry teachers based on school status with significance level of 0.783. The effect size test shows that the partial eta square value for the effect of teaching experience belongs to the high category while school status belongs to the low category.